E-PAYMENT: INOVASI LAYANAN PENGHIMPUNAN DAN REDISTRIBUSI WAKAF UANG BERBASIS ONLINE DALAM PERCEPATAN PEMBANGUNAN EKONOMI INDONESIA - Berakon, Izra; Irsad, Agus Muhammad (AL-QARDH, 2017)
Indonesia as a majorMuslim population country, has a large potential of cash waqf. Indonesian Waqf Board (BWI) predicted the potential of cash waqf in Indonesia is Rp 20 trillion, but had not followed by the effective collection method, so that potential has not been able to develop optimally. On the other hand, technology grown rapidly, followed by the numberof internet users in Indonesia. Based on the data of